Candle soot: Journey from a pollutant to a functional material. (April 2019) - Mulay, Manasi R.; Chauhan, Aditya; Patel, Satyanarayan; Balakrishnan, Viswanath; Halder, Aditi; Vaish, Rahul
Abstract: Candle soot, traditionally considered as an unwanted source of air-pollution, has slowly been phased out by modern lighting techniques. However, a 2007 study by Liu and co-workers first brought to light the presence of fluorescent carbon nanoparticles (CNPs) in untreated candle-soot (CS). Subsequent studies revealed that these soot-generated CNPs can be refined and extracted for various applications including humidity sensing, trace element detection and biomedical to Li-ion batteries, supercapacitors, electrocatalysis and solar collector among others. There are over 100 published articles dealing with fabrication, extraction, treatment and application of CS derived CNPs. However, unlike traditional carbon-based nanostructures including graphene and fullerene, this field lacks the presence of a systematic endeavour to tap into the vast potential of candle-soot. Therefore, this article aims to present a focused review on the topic of CS derived CNPs and their potential applications. The paper starts with a brief introduction on the topic of candle-soot and its historic significance. This is followed by a description of the techniques used to extract, refine and functionalize these carbon particles. Thereafter the reported applications of candle-soot derived nanostructures and their comparative analysis with the current state-of-art are provided. Finally, a section discussing future scopes and challenges is presented followed by conclusions. Graphical abstract: Image 1